Emergency Bedside Transvenous Pacing Without Fluoroscopic Guidance for Refractory Symptomatic Bradycardia Following Cardiac Arrest in Acute Inferior ST-Elevation Myocardial Infarction: A Case Report - Philipus Wiranata; Michael Sebastian Kawilarang (HM Publisher, 2026)
Background: Symptomatic bradycardia is a recognized complication of acute inferior myocardial infarction due to atrioventricular node ischemia. Temporary transvenous pacemaker insertion traditionally requires fluoroscopic guidance, which may be unavailable in emergency departments. Alternative non-fluoroscopic approaches are essential in time-critical, resource-limited settings. Case presentation: A 62-year-old male with uncontrolled diabetes mellitus presented to the emergency department with respiratory and cardiac arrest. Following cardiopulmonary resuscitation, return of spontaneous circulation was achieved. Electrocardiography revealed inferior ST-elevation myocardial infarction with second-degree atrioventricular block type II. Despite administration of atropine sulfate (cumulative dose 1.25 mg intravenously) and vasopressor support, the patient developed refractory symptomatic bradycardia with heart rate declining to 25-30 beats per minute, culminating in a second cardiac arrest. After achieving return of spontaneous circulation for the second time, a temporary transvenous pacemaker was inserted at the bedside in the emergency department via the femoral vein using a blind technique with electrocardiographic monitoring as the sole guide for successful placement. The pacemaker was set to VVI mode at 70 beats per minute. Subsequent fluoroscopic confirmation in the catheterization laboratory revealed the catheter tip in the right ventricular outflow tract, which was repositioned to the right ventricular apex. Percutaneous coronary intervention was subsequently performed. Conclusion: Bedside blind temporary transvenous pacemaker insertion using electrocardiographic monitoring is a feasible and effective approach in emergency settings where fluoroscopic guidance is unavailable.